"Show me the money plan!" - Chard, Chris (London : Human Kinetics, Inc., 2014)
Rich Smith has just signed his last professional contract in the National Hockey League (NHL). He and his wife, Sarah, however have never operated within a budget or devised a plan to ensure their lifestyle will not suffer after Rich retires. To assist them in achieving their goals (no debt and $8 million in investment assets), Rich hires Clarke Redmond of Redtail Sports Management (RSM). This case analyses the actions taken thereafter.
Originally published in Chard, C. (2014). "Show Me the Money Plan!" Case Studies in Sport Management, 3(1), 33-38. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Smith, Rich; Smith, Sarah; Redmond, Clarke; Investments; Finance, Personal; Saving and investment